ProteomicsDB: toward a FAIR open-source resource for life-science research. Issue Volume 50:Issue D1(2022) (17th November 2021) - Lautenbacher, Ludwig; Samaras, Patroklos; Muller, Julian; Grafberger, Andreas; Shraideh, Marwin; Rank, Johannes; Fuchs, Simon T; Schmidt, Tobias K; The, Matthew; Dallago, Christian; Wittges, Holger; Rost, Burkhard; et al.
Abstract: ProteomicsDB (https://www.ProteomicsDB.org ) is a multi-omics and multi-organism resource for life science research. In this update, we present our efforts to continuously develop and expand ProteomicsDB. The major focus over the last two years was improving the findability, accessibility, interoperability and reusability (FAIR) of the data as well as its implementation. For this purpose, we release a new application programming interface (API) that provides systematic access to essentially all data in ProteomicsDB. Second, we release a new open-source user interface (UI) and show the advantages the scientific community gains from such software. With the new interface, two new visualizations of protein primary, secondary and tertiary structure as well an updated spectrum viewer were added. Furthermore, we integrated ProteomicsDB with our deep-neural-network Prosit that can predict the fragmentation characteristics and retention time of peptides. The result is an automatic processing pipeline that can be used to reevaluate database search engine results stored in ProteomicsDB. In addition, we extended the data content with experiments investigating different human biology as well as a newly supported organism.